2017
DOI: 10.1080/01694243.2017.1349716
|View full text |Cite
|
Sign up to set email alerts
|

Adherability and weldability of poly(lactic acid) and basalt fibre-reinforced poly(lactic acid)

Abstract: The adherability and weldability of pure poly(lactic acid) (PLA) and basalt fibre-reinforced PLA were investigated in this research. The joining efficiency rate is introduced as a comparative parameter among different joining processes. In the case of adhesive bonding, 16 different adhesives were used to join specimens together. The highest bond strength and joining efficiency rate for both the pure (16 MPa, 78%) and basalt fiber-reinforced (18 MPa, 44%) adhesive-bonded specimens was achieved with acrylate-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…To achieve high strength, fibers are selected, among which the basalt fiber (BF) plays an important role in reinforcing the composite. 1315 Many studies reveal that the inclusion of BF increases the physical and mechanical properties, hence it is the best reinforcing agent for polymer composites. 16 Basalt is one of the promising materials for reinforcement due to its vast beneficial properties, including high strength, rigidity modulus, high heat resistance, and damping.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve high strength, fibers are selected, among which the basalt fiber (BF) plays an important role in reinforcing the composite. 1315 Many studies reveal that the inclusion of BF increases the physical and mechanical properties, hence it is the best reinforcing agent for polymer composites. 16 Basalt is one of the promising materials for reinforcement due to its vast beneficial properties, including high strength, rigidity modulus, high heat resistance, and damping.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to the use of chemical adhesives, some authors suggested an innovative research line based on the joining of PLA components by the supply of focused energy over reduced areas. For this purpose, the use of laser techniques can achieve the heat transfer control for the melting of localized areas of plastic materials, facilitating the bonding process of both elements [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to the use of chemical adhesives, some authors suggest an innovative research line based on the joining of PLA components by the supply of focused energy over reduced areas. For this purpose, the use of laser techniques can achieve the heat transfer control for the melting of localized areas of plastic materials, facilitating the bonding process of both elements [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%